2023
DOI: 10.3389/fpsyt.2022.1086026
|View full text |Cite
|
Sign up to set email alerts
|

Juror characteristics on trial: Investigating how psychopathic traits, rape attitudes, victimization experiences, and juror demographics influence decision-making in an intimate partner rape trial

Abstract: IntroductionTrial by jury is a longstanding legal tradition used in common law jurisdictions to try the most serious of criminal cases. Yet, despite hearing the same trial evidence, individual jurors often arrive at different verdict decisions, indicating that they may be impacted by more than the evidence presented at trial. This study therefore sought to investigate the role of jurors’ psychopathology, attitudinal, experiential, and demographic characteristics upon individual verdict decisions.MethodsAdoptin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 74 publications
1
11
1
Order By: Relevance
“…Given these questions were originally posed within Canada it may be that age differences present differently within a British criminal justice context. The current finding is in line with studies completed within the UK on specific case types, including those exploring sexually violent crimes and elements of vulnerability, which found younger individuals show more victim sympathy (Lilley et al 2023a;Ioannides and Willmott 2024;Smith et al 2022). Therefore, age differences in victim treatment attitudes may be impacted by the type of victimisation.…”
Section: Perceptions Of Victim Treatmentsupporting
confidence: 87%
See 2 more Smart Citations
“…Given these questions were originally posed within Canada it may be that age differences present differently within a British criminal justice context. The current finding is in line with studies completed within the UK on specific case types, including those exploring sexually violent crimes and elements of vulnerability, which found younger individuals show more victim sympathy (Lilley et al 2023a;Ioannides and Willmott 2024;Smith et al 2022). Therefore, age differences in victim treatment attitudes may be impacted by the type of victimisation.…”
Section: Perceptions Of Victim Treatmentsupporting
confidence: 87%
“…However, public opinion on the appropriate treatment of these groups can differ from the official position. A wide range of factors have been found to impact attitudes towards victims and defendants, relating to fear of crime, victimisation, empathy, demographics characteristics, and broader justice attitudes (Chockalingam and Srinivasan 2008;Cook and Duff 2023;Conroy et al 2023;Debowska et al 2019;Lilley et al 2023aLilley et al , 2023bLucas et al 2011). Opinion on appropriate treatment also varies depending on the individual case, including the alleged offence type and characteristics of the victim and accused (Devine and Mojtahedi 2021;Sowersby et al 2022).…”
Section: Attitudes Towards Victims and Defendants In Courtmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, to gain further insight into the motives and psychological antecedents child abductions, clinical research should study the role of dark traits (e.g. psychopathy) and criminal cognitions (DeBlasio and Mojtahedi, 2023; Lilley et al , 2023) within NFA samples.…”
Section: Discussionmentioning
confidence: 99%
“…In their work, judges are driven not only by legal factors but also by extralegal ones, including, but not limited to the age of the defendant, his/her sex, race, or ethnic origin or the nature of his/her profession (Freiburger, 2010;Freiburger and Hilinski, 2013;Hilinski-Rosick et al, 2014;Van Slyke and Bales, 2013). Indeed, judges are not unique in this regard, as several recent studies have found similar legal and extra-legal influences also impact upon lay decision-makers within common law adversarial legal systems (Ballot et al, 2021;Hudspith et al, 2023;Lilley et al, 2023;Willmott and Sherretts, 2016;Willmott et al, 2018). The research in this field focusses particularly on the sex of the defendant.…”
mentioning
confidence: 99%